We Should Not Be a Counterpart Theorist of Events If We Want to Be a Counterfactual Theorist of Causation - Tang, Zhiheng (Theoria (Lund, Sweden), 2021)
Although David Lewis advocates a counterpart‐theoretic treatment of objects but rejects a parallel treatment of events, many philosophers have — mainly to solve some puzzles within the framework of a Lewisian counterfactual analysis of causation — suggested that the counterpart‐theoretic treatment be extended to events. This article argues that we had better not be a counterpart theorist of events as long as we want to remain at all faithful to the counterfactual analysis of causation.